Enklave bahasa Toraja pada anak imigran Indonesia di wilayah Sabah, Malaysia - Christmatara, Candraderi; Suryadi, Muhammad (Universitas Mulawarman, 2024)
This research examines the use of the Toraja language spoken by children of Indonesian immigrants in Sabah, Malaysia. This phenomenon is unique because these children, who are of Toraja descent and born also raised in an environment where Malay Sabah is the primary language of communication, maintain the use of the Toraja Language. The purpose of this research is to present the forms of Toraja language enclaves in Sabah, Malaysia. This research employs a qualitative descriptive method. Data sources were collected using purposive sampling. Data collection techniques included observation, interviews, and elicitation. The three stages of analysis involved data reduction, data presentation, and conclusion drawing. The results showed that Indonesian immigrant children born and raised in the Sabah, Malaysia, use both the Toraja language and Malay Sabah in various domains. The analysis revealed that Indonesian immigrant children have a better understanding of Malay Sabah than the Toraja language, influenced by economic, social, cultural, and topographical factors.